PENERAPAN PELAPORAN SPT TAHUNAN PPH ORANG PRIBADI MENGGUNAKAN CORETAX PADA KANTOR KONSULTAN PAJAK NURLENA, CHARLES DAN REKAN - Arya, Dimas; Murnidayanti, Scheilla Aprilia (Jurusan Akuntansi FEB Universitas Jambi, 2026)
This research is entitled ‘The Implementation of Annual Personal Income Tax Return Filing Using Coretax at the Nurlena, Charles and Partners Tax Consultancy’. The method used in writing this report is a qualitative descriptive method, with data collection techniques including participatory observation during the internship, interviews, and a literature review. The research findings indicate that the implementation of Coretax has brought about significant transformation through its pre-populated features, which enhance efficiency, accuracy, and the integration of tax data. However, several technical challenges were identified during implementation, such as server infrastructure instability during peak filing periods, discrepancies between automated data and physical documents, and limitations in taxpayers digital literacy. The tax consultancy firm Nurlena, Charles and Partners played a strategic role in mitigating these challenges through data validation functions and technical assistance to ensure clients’ tax compliance remained in line with applicable regulations.